Ethnic Identity, Self-esteem, and Academic Performance of Nigerian In-school Adolescents - Adams Ogirima Onivehu (Pedagogika, 2022)
The development of ethnic identification plays an integral role in the formation of the self among in-school adolescents, especially in Nigeria, which is largely a multicultural and multi-ethnic nation. Thus, the present study investigated the extent to which ethnic identity and self-esteem could predict academic performance among Nigerian in-school adolescents.